Technological capability assessment of a firm in the electricity sector - Panda, H. (Technovation)
The importance of technological capability enhancement in today's highly competitive and demanding business environment is well accepted. This paper proposes a methodology to assess the elements of strategic, tactical and supplementary capabilities, all of which together constitute the technological capability of a firm. In addition, the methodology includes the assessment of the steering capability of the firm in its analytical framework. The proposed methodology comprises five steps : identification of value addition stages performed by a firm; determination of technological capabilities needed at these stages; development of indicators for assessing the identified technological capabilities; benchmarking the capabilities assessed with a state-of-the-art firm; and analysis of the reasons for the technological capability gap between the firm being studied and the state-of-the-art firm. The development of the indicators is illustrated using a firm from the electricity sector. Some suggestions are then made as to how the assessment exercise can be used for technological capability enhancement planning. Special attention is paid to specific external and internal factors that can influence technological capability enhancement. Policy makers are often interested in examining the benefits and disbenefits of assessment exercises such as the one proposed in this paper. This aspect is also addressed briefly and some suggestions are made as to how problems, that could arise out of the findings of the assessment exercises, may be managed.